Menstrual Hygiene and Academic Performance of Adolescent Girls in Arua City Schools: A Case Study of Anyafiyo Primary School - Gloria Samuel Joel Modong (Uganda Christian University, 2025)
About 1.8 billion women worldwide are menstruating, with an estimate of about 800 million who lack access to menstrual hygiene materials and adequate facilities for effective Menstrual Hygiene Management. Girls and women within the cycle need easy access to menstrual hygiene materials, general information on good practices and above all supportive environment where they can easily manage their menstrual cycles without fear especially the adolescents in terms of water, sanitation and hygiene (WASH) facilities. The aspect of the menstrual management is so sensitive that needs lots of resource to ensure healthy practice for the betterment of woman’s body. However, it’s of great concern that about 52% girls and women lack access to health practice of the (MHM) (World Bank 2022) and it is worst in the low-income countries where a half of the schools lack adequate water, sanitation and hygiene services which are so crucial to enable girls and even the female teachers to manage menstruation. (UNICEF 2015). Therefore, the research aim was to explore menstrual hygiene management on/and academic performance of adolescent girls relating to how menstrual management has contributed to the poor academic performance of the adolescent girls in Anyafiyo Primary School. Therefore, with basic efforts to create more awareness, information and knowledge on MHM among the adolescent, efforts to ensure better hygienic materials and places and innovative skills on how to use the available materials (Lenia et al 2019). Hence a study to understand the lack of information regarding the menstrual hygiene management among the adolescents leading to their poor academic performance.
Undergraduate